2014
DOI: 10.5897/ajbr2013.0732
|View full text |Cite
|
Sign up to set email alerts
|

The composition of fatty acids stored in liver, muscle and fat tissues of the African lungfish Protopterus annectens (Owen, 1839)

Abstract: The composition and profile (%) of fatty acids stored in liver, muscle, and fat tissues of the fresh-water African lungfish Protopterus annectens were determined by gas chromatography. High content of total fatty acids (TFA) was found in fat (62.06 ± 3.4 g/100 g) followed by liver (50.68 ± 4.72 g/100 g) and muscle tissues (10.9 ± 0.81 g/100 g). Saturated fatty acids (SFA) formed 72.9% TFA in the liver and muscles and 53.3% in fat. Fat was rich in polyunsaturated fatty acids (PUFA), containing 31.1%, while musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
0
3
Order By: Relevance
“…The total acid value (TAV) was slightly higher in Protopterus annectens than Heterotis niloticus in the current study. This result conflicts with the previous studies on P. annectens from other regions 16 . Oleic acid (C18:1), a monosaturated omega-9 fatty acid is the most abundant fatty acid in P. annectens and H. niloticus in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The total acid value (TAV) was slightly higher in Protopterus annectens than Heterotis niloticus in the current study. This result conflicts with the previous studies on P. annectens from other regions 16 . Oleic acid (C18:1), a monosaturated omega-9 fatty acid is the most abundant fatty acid in P. annectens and H. niloticus in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the work of Osibona et al 8 , who reported that C18:1was the dominant fatty acid in Clarias gariepinus and Tilapia zilli from Makoko and Epe Landing sites in Lagos, Nigeria. When compared with muscle oleic acid contents in P. annectens (0.82±029 g 100 gG 1 ) and H. niloticus (21.42±0.14 g 100 gG 1 ) reported by the previous study 16,17 the content of fatty acid in the current study were lower. Also, the oleic level in this study was comparatively low to the values reported in four freshwater fish species from Maga Lake, Cameroon 17 .…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation